Efficacy of BRAF‐Inhibitor Therapy in BRAFV600E‐Mutated Adult Langerhans Cell Histiocytosis. (12th October 2020) - Hazim, Antonious Z.; Ruan, Gordon J.; Ravindran, Aishwarya; Abeykoon, Jithma P.; Scheckel, Caleb; Vassallo, Robert; Ryu, Jay H.; Tobin, W. Oliver; Koster, Matthew J.; Bennani, N. Nora; Rech, Karen L.; Young, Jason R.; et al.
Abstract: Langerhans cell histiocytosis (LCH) is a rare histiocytic neoplasm. To date, there is a lack of U.S. Food and Drug Administration–approved treatments in adult LCH to establish optimal first‐line therapy. We conducted a retrospective, single‐center case series evaluating the use of BRAF inhibitors in adult patients with BRAF V600E ‐ LCH proven by biopsy. Our case series is the first to report the use of BRAF inhibitors as first‐line therapy in adults with LCH. We also report the efficacy with single‐agent dabrafenib in adult LCH. All but one of our patients had favorable response to targeted therapy. Abstract : Optimal first‐line treatment for Langerhans cell histiocytosis (LCH) has not been established. This case series evaluates the use of BRAF inhibitors in adult patients with LCH.